The Use of Neuron Networks for the Performance of Epidemics Caused by Computer Viruses - Laurutis, R.; Puniškis, D. (Elektronika ir Elektrotechnika, 2004)
Computer viruses are the representatives of the first artificial intelligence. They are able to spread unrestrictedly within the networks of telecommunications, computers and in the near future within GSM. Epidemics caused by viruses in the networks occur more and more frequently bringing ominous problems of computer systems, while modern microscopic technologies are unable to stop them effectively. Microscopic virus detecting technology appealing to the observation of users’ behaviour is reviewed in the article. Neuron newtorks are used for analysis as they are indoctrinated with “normal” and “abnormal” behaviour of users. The neuron network observes e-mails of the users in the real time and decides whether a user behaves normally or not. It was proved by experiment that this technology is effective but still it needs to be improved in order to reduce the number of invalid decisions. Ill. 7, bibl. 10 (in Lithuanian, summaries in Lithuanian, English and Russian).